PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI BANK BRI SYARIAH KABUPATEN SUBANG - Opan Arifudin; Fenny Damayanti Rusmana (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2020)
An Islamic banking institution that wants to carry out its duties and functions well, will try to change its employees so that they have good performance. This is done so that its employees are more productive in carrying out their duties and responsibilities. To get employees in accordance with what is expected, it is necessary to have a working environment that supports the implementation of tasks, namely the work environment in terms of infrastructure, as well as the general environment, namely the community in Islamic banking institutions. Data collection methods in research are methods or methods used by researchers to obtain data in a study. Data collection methods in this study using the Questionnaire Method. the significance value of Individual Characteristics is 0,000 smaller than the significance level (α) 0.05. Because the value of t count> t table (5.632> 2.020) and the significance value is smaller than the significance level (α) 0.05 (0.000 <0.05), the second hypothesis is accepted, meaning that Individual Characteristics has a positive and significant effect on employee performance. The third hypothesis is accepted, meaning that the Work Environment and Individual Characteristics simultaneously have a positive and significant effect on employee performance. This is shown because the calculated F value> F table (34.254> 3.226) and the significance value is smaller than the significance level (α) 0.05 (0.000 <0.05).